Editorial: Tales of Multiple Decolonisations - Singh, Prabhakar (UI Scholars Hub, 2022)
The dialectics between descriptions and solutions should now animate TWAIL scholarship. A crucial aspect of TWAIL is to debate racism in south-south relations and law. TWAIL also needs to ask if former victims, having secured sovereignty during de-colonisation, are attempting to secure an empire.